Study on Compliant Actuator of the Knee Joint for Exoskeleton - Pingxin Ji; Peng Song; Xinmin Mo; Zuba Wei; Hao Zhao (Jixie chuandong)
The compliance of the joint for exoskeleton is very important in adapting to the wearer's motions and human-machine compatibility. However，the conventional rigid or passive compliant mechanisms cannot achieve the purpose of active compliance due to the non-real-time feedback of the human-machine interaction forces. Therefore，an active compliant actuator of the knee joint is developed，using of the antagonistic driving principles and the force-position transformation of the slider-crank mechanism，which can not only implement the compliance of the traditional series elastic actuator，but also can obtain the real-time human-machine interaction forces. Finally，the feasibility and effectiveness of the compliant actuator are verified by tests.